'A fair go for all?' Australia's language-in-migration policy. Issue 6 (2nd November 2017) - Hoang, Ngoc T. H.; Hamid, M. Obaidul
ABSTRACT: As the power of tests lies in their uses, language tests that are used to assess immigration eligibility exercise enormous power. Critical Language Testing calls for exposing the power of tests by examining the intentions of introducing tests and their effects on individuals and society, especially from the perspective of test-takers. This case study investigates the rationale for and impact of a particular language-in-migration policy in Australia, drawing on the experiences and perceptions of two skilled migration applicants. One of them was successful and the other unsuccessful, essentially on the ground of their language test results. Insights from the study challenge prevalent discourses about language tests and social integration, employability, economic efficiency, and national security. The article makes some policy recommendations for making the use of language tests more beneficial for immigrants and immigrant-receiving societies in a globalised world that has witnessed unprecedented flows of immigrants.